Efficient inhibition of cyanobacteria M. aeruginosa growth using commercial food-grade fumaric acid. (August 2022) - Wei, Peiyun; Ma, Hanmin; Fu, Heyun; Xu, Zhaoyi; Qu, Xiaolei
Abstract: The control of cyanobacteria blooms is a global challenge. Here, we reported the efficient inhibition of M. aeruginosa by fumaric acid (FA), an intermediate metabolite of the tricarboxylic acid cycle. FA showed strong algicidal activity with an inhibition rate of 90.5% on the 8th day at a dose of 40 mg/L. The presence of FA caused severe membrane damage, as suggested by the fluorescence flow cytometry and morphology analysis. FA inhibited the formation of chlorophyll a, interrupting the photosynthesis system. It also induced oxidative stress in cells. Principal component analysis of the indicators suggested that the FA-treated sample had a significantly different inhibitory pattern than the acid-treated sample. Thus, the inhibitory effect was not solely caused by the pH effect. Untargeted metabolomic analysis revealed that 31 metabolites were differentially expressed in response to FA stress, which were mainly involved in the metabolite processes and the membranes. A commercial food-grade FA was able to inhibit the growth of M. aeruginosa similar to the analytical-grade FA. Our results suggest that FA can be potentially an efficient and low-risk chemical for inhibiting M. aeruginosa growth, which may find future applications in cyanobacteria bloom control. Graphical abstract: Image 1 Highlights: Fumaric acid can strongly inhibit the growth of Microcystis aeruginosa . Fumaric acid caused sever and irreversible cell membrane damages. Fumaric acid caused oxidative stresses and reduced the photosynthetic activity. Commercial food-grade fumaric acid had the same performance as the reagent.